Simulação da fadiga em materiais utilizando a peridinâmica - (:unkn) unknown (Universidade Federal do Pampa, 2024)
Since the 19th century, structures composed of metallic materials have faced technical challenges resulting from fatigue failures, emerging as one of the main concerns in the aeronautical sector. In this context, structural components often encounter repeated loads, resulting in microscopic damage. However, fatigue is not restricted only to metals and metallic alloys, it can also occur in rocks and concrete, categorized as quasi brittle materials. Unlike metallic components, there is a notable lack of studies dedicated to fatigue in this context. Thus, this research focuses on the application of peridynamics as a tool to simulate the phenomenon of fatigue in quasi brittle materials. Given this scenario, the study presents a theoretical basis that encompasses the fundamental categories of material failures, the phenomenon of fatigue, the principles of the Paris Law and the foundations of peridynamics. The final objective is to evaluate the feasibility of a peridynamic model capable of incorporating the effects of cyclic loads, estimating the useful life under fatigue conditions for materials with quasi brittle characteristics and determining the parameters relevant to the Paris Law. This research aims to fill a gap in the understanding of fatigue in quasi brittle materials, thus seeking to contribute to the development of efficient strategies for analyzing and preventing failures in these materials.
Keywords: Engenharia mecânica; Fadiga; Peridinâmica; Mechanical engineering; Fatigue; Perydinamics; CNPQ::ENGENHARIAS